An Investigation into the Effect of Joint Frequency and Spacial Positioning on Pre-Splitting - Syed M. Tariq; Paul N. Worsey (International Society of Explosives Engineers, 1995)
Pre-splitting is now widely used to minimize overbreak and to protect final surface rock excavation profiles in large scale civil construction projects, open pit mining and quarrying. Jointing has been shown to affect the success of pre-splitting and the smoothness and integrity of the resulting rock face. Many facets of jointing have been investigated in detail, including the inclination of joints with respect to the desired pre-split plane, the effects of various filling materials, etc. However, the effects of joint frequency and spatial positioning has been paid little attention. The paper addresses this issue.